Promoting civic engagement among students in the preservation of local culture during a time of disruption - Indriyani, Dina; Komalasari, Kokom; Malihah, Elly; Fitriasari, Susan (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Citizenship education aims to cultivate intelligent and responsible citizens. One essential characteristic of a responsible citizen is their active engagement in civic duties, as demonstrated through their attitudes and behavior. This study examines the level of civic engagement among high school students in preserving local culture during the era of disruption. The research adopts a quantitative descriptive approach and collects data from high school students in Cianjur Regency, Indonesia, using a survey questionnaire. The findings reveal that: (1) the level of civic attitude among students in cultural preservation is sufficient, with a score of 55.12%; and (2) the level of civic behavior, specifically real action taken to preserve local culture, is very low, with a score of 9.22%. This suggests that student involvement in cultural preservation needs to be further developed to safeguard local culture. Therefore, future researchers are advised to devise a Citizenship education learning model that can foster civic engagement among high school students in preserving local culture.